Redesigning landscape architecture in higher education: a multimodal social semiotic approach - Price, Christine Rosalie (School of Education, 2021)
This investigation is a case study of landscape architectural design education in South Africa. Current forms of landscape architectural education are influenced by Global North perspectives and often, if not consciously, privilege particular ways of meaningmaking, and exclude or marginalise experiences or ways of knowing that are different. The aim of this research is to develop a landscape architectural pedagogy for diversity that fosters multiple perspectives and valorises resources that students bring to their learning environment, in order that students may both access and challenge the dominant landscape educational discourse. In grappling with these concerns, this research finds resonance with a multimodal social semiotic approach. Instead of labelling students as (in) competent or (under)prepared, a multimodal social semiotic approach emphasises the interest, agency and resourcefulness of the student as meaning-maker. The research thus reframes landscape architectural design processes through a multimodal social semiotic lens, providing new insights and clarity to these processes. The approach foregrounds interpersonal and social meanings of space and, to some extent, challenges traditional landscape architectural design practices that tend to value compositional and conceptual meanings. The methodology centers around a spatial model project in the second half of a first-year landscape architectural design studio subject. The data includes students' texts and their presentations. The research develops a methodological framework that outlines a range of ideational, interpersonal and textual meaningpotentials of landscape spatial and visual texts and applies this framework to the analysis of students' 2D and 3D texts. Through careful analysis of students' design trajectories, this research uncovers the types of resources students draw on, including semiotic, experiential, social, interactive and pedagogical resources. The analysis shows that students' transformation of resources results in innovative spatial designs, and expands on what and how landscape spaces can mean. Through the investigation, tenets for a multimodal pedagogy for diversity are developed: recognition of the rich and diverse resources students bring to their learning environment; acknowledgment that these resources are apt ‘precedent' for landscape architectural design processes; and explicit attention to multimodal moments and activities that may prompt re-(inner) conceptualisation in design trajectories. This pedagogical approach begins to address past educational imbalances and inequalities, and ensures that diverse, Global South perspectives contribute to the production of knowledge.